Widespread occurrence of endogenous cellulase production and glycosyl hydrolase in grapsoid crabs along the land-sea transition indicates high potential for mineralisation of mangrove production - Lee, Cheuk Yan; Lee, Shing Yip (Frontiers in Marine Science, 2022)
Previous studies on mangrove carbon utilisation and mineralisation were focused on mangrove sesarmid crabs (Grapsoidea: Sesarmidae) because they are initial processors of mangrove organic carbon. Grapsoid crabs from other families and habitats were generally ignored although they also perform various levels of herbivory. It remains unclear how the herbivorous crabs utilise the production from mangrove or vascular plants because of the high C/N ratio and high structural carbon content of these materials. In this study, production of cellulase and expression of hepatopancreatic glycosyl hydrolase of grapsoid crabs were investigated in a more extensive way in terms of their taxa (15 species) and habitats (i.e., land margin, mangrove, mudflat, and subtidal area). Generally, low gastric endoglucanase (1.46-2.98 μmol min−1 ml−1) and β-glucosidase (0.06-0.61 μmol min−1 ml−1) activity was detected in 15 grapsoid crabs distributed along the land-sea transition. The activity of both enzymes was significantly affected by the taxonomic affiliation and habitat of the crabs: endoglucanase in sesarmids > varunids > grapsids; and land margin, mangrove and limnic habitats > mudflat and subtidal area. For β-glucosidase: sesarmids > varunids and grapsids; and land and limnic > mangrove and subtidal > mudflat. Our detection of gastric cellulases in mudflat and subtidal grapsoid crabs has rarely been reported. These results show that there is a need to re-evaluate the role of crabs from these habitats in mangrove/vascular plant carbon mineralisation. Further, low cellulase activity could be a common trait among crabs along the land-sea transition and the importance of cellulase in vascular plant carbon utilisation could have been previously over-rated. Glycosyl hydrolase family 9 (GH9) genes were identified in the hepatopancreatic transcriptome of all 15 species, indicating endogenous production of cellulase. In addition, the presence of other digestive carbohydrate-active enzymes (CAZymes), including GH5_10, GH13, GH13_24, and GH16, suggests that a capacity for the utilisation of carbon sources other than cellulose by the grapsoid crabs, which may enable sufficient assimilation of vascular plant carbon despite the low cellulase activity.